STRATEGI KOMUNIKASI POLITIK MELALUI MEDIA SOSIAL YOUTUBE DALAM MENINGKATKAN ELEKTABILITAS AHOK - Iwan Setiawan (Universitas Mercu Buana, 2017)
In this study, researchers wanted to delve into the strategy of political communication which is run through social media in this regard youtube for the career development and the political influence of a politician in pursuit of political office in this country. Youtube chosen than others, due to social media is social media youtube video so there are similarities with the television media, but the cost to use the youtube media is much cheaper than when a politician uses television. And although it costs much cheaper, but the effects of a viral youtube as a part of social media is very significant. This is because youtube easily distributed to the public in very large numbers and across borders. Youtube effectiveness in reaching audiences seemed destined to politicians who quite phenomenal figure in this country with the program of work and controversy that makes the figure Ahok the center of attention for many people across the country. It is interesting for researchers to dig deeper into the communications strategy in the run of a Ahok in improving his elektability especially in local elections in 2017 DKI this via youtube.Keywords: Political communication, social media, Youtube, DKI election, Elektability